2010
DOI: 10.1371/journal.ppat.1001144
|View full text |Cite
|
Sign up to set email alerts
|

Early Production of IL-22 but Not IL-17 by Peripheral Blood Mononuclear Cells Exposed to live Borrelia burgdorferi: The Role of Monocytes and Interleukin-1

Abstract: If insufficiently treated, Lyme borreliosis can evolve into an inflammatory disorder affecting skin, joints, and the CNS. Early innate immunity may determine host responses targeting infection. Thus, we sought to characterize the immediate cytokine storm associated with exposure of PBMC to moderate levels of live Borrelia burgdorferi. Since Th17 cytokines are connected to host defense against extracellular bacteria, we focused on interleukin (IL)-17 and IL-22. Here, we report that, despite induction of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 89 publications
2
36
0
1
Order By: Relevance
“…In addition, there is increasing evidence that IL-22 is likewise a vital product of activated CD8 ϩ T cells (7)(8)(9). IL-22 is derived from either T cells or innate sources, specifically natural killer cells, CD11 ϩ dendritic cells, and heterogeneous lineages of innate lymphoid cell populations (10,11) and apparently fulfills a fundamental function as messenger between leukocytic and non-leukocytic cell compartments.…”
mentioning
confidence: 99%
“…In addition, there is increasing evidence that IL-22 is likewise a vital product of activated CD8 ϩ T cells (7)(8)(9). IL-22 is derived from either T cells or innate sources, specifically natural killer cells, CD11 ϩ dendritic cells, and heterogeneous lineages of innate lymphoid cell populations (10,11) and apparently fulfills a fundamental function as messenger between leukocytic and non-leukocytic cell compartments.…”
mentioning
confidence: 99%
“…It is thought to play an important role in the pathogenesis of rheumatoid and osteoarthritis (40); however, it is also an important regulator of host defense through granulopoiesis and neutrophil recruitment (41). Several studies have proposed that IL-17 may play a role in neuroborreliosis and Lyme arthritis in humans (19,20), although this remains controversial (17,18). Using a murine vaccination and challenge model system, others have found that IL-17 directly impacts Lyme arthritis development (22).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the correlation between B. burgdorferi exposure and IL-17 production is not as clear. Stimulation of peripheral blood mononuclear cells (PBMC) from normal donors did not induce IL-17 production (17), and no serum IL-17 could be detected in B. burgdorferi antibody-positive asymptomatic children (18). In contrast, IL-17 can be found in the cerebrospinal fluid of neuroborreliosis patients (19) and synovial T cells produce IL-17 in response to stimulation with the neutrophil-activating protein A (NapA) of B. burgdorferi (20).…”
mentioning
confidence: 99%
“…Many studies have shown that cytokines play an important role in the pathogenesis of Lyme borreliosis in the initial phase of infection (Miller et al 2008, Rupprecht et al 2009, Bachmann et al 2010), while at late infection expression of some, especially Th1-associated cytokines, waned (Sjowall et al 2011). One of the most investigated cytokines is IL-10, which was slightly overexpressed (Benhnia et al 2005, Lazarus et al 2008, and has been shown to be a main cytokine to regulate inflammatory response in B. burgdorferi infection (Gautam et al 2011).…”
Section: Discussionmentioning
confidence: 99%